2015
DOI: 10.1016/j.devcel.2015.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of Primary Cilia by Proximity Labeling

Abstract: SUMMARY While cilia are recognized as important signaling organelles, the extent of ciliary functions remains unknown because of difficulties in cataloguing proteins from mammalian primary cilia. We present a method that readily captures rapid snapshots of the ciliary proteome by selectively biotinylating ciliary proteins using a cilia-targeted proximity labeling enzyme (cilia-APEX). Besides identifying known ciliary proteins, cilia-APEX uncovered several ciliary signaling molecules. The kinases PKA, AMPK and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
403
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 359 publications
(435 citation statements)
references
References 78 publications
21
403
1
1
Order By: Relevance
“…Until recently, PKA was thought to phosphorylate Gli proteins at the base of cilia under basal or SHH-off conditions due to PKA-C localization there (5). Several PKA subunits were recently detected within the cilium using cilia proximity labeling, and PKA-R1α was detected within cilia using immunofluorescence (6). Additionally, by specifically inhibiting PKA activity within cilia, Mick et al found that ciliary PKA activity is necessary for proper Gli3 protein processing (6).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Until recently, PKA was thought to phosphorylate Gli proteins at the base of cilia under basal or SHH-off conditions due to PKA-C localization there (5). Several PKA subunits were recently detected within the cilium using cilia proximity labeling, and PKA-R1α was detected within cilia using immunofluorescence (6). Additionally, by specifically inhibiting PKA activity within cilia, Mick et al found that ciliary PKA activity is necessary for proper Gli3 protein processing (6).…”
Section: Resultsmentioning
confidence: 99%
“…Several PKA subunits were recently detected within the cilium using cilia proximity labeling, and PKA-R1α was detected within cilia using immunofluorescence (6). Additionally, by specifically inhibiting PKA activity within cilia, Mick et al found that ciliary PKA activity is necessary for proper Gli3 protein processing (6). We targeted a PKA activity sensor, AKAR4 (19), to the cilia using the 5HT6 receptor (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MiniSOG is a fluorescent flavoprotein that, when genetically encoded, is used as a versatile tag that emits fluorescence and, in response to illumination, generates singlet oxygen that transforms diaminobenzidine into electron-dense precipitates that can by imaged by using EM. The engineered peroxidase APEX, by contrast, can be used for EM and proximity labeling upon its fusion to a protein of interest, (Mick et al, 2015). Alternatively, events or regions of interest can be tracked over the two imaging modalities, with recording of coordinates imprinted on the culture dish, by using either commercialized (Al Jord et al, 2014) or lasermicropatterned culture substrates (Spiegelhalter et al, 2010).…”
Section: Ground-breaking In Vitro Clemmentioning
confidence: 99%